Secondary orientation effect of the platform defects in [001] oriented single crystal blades prepared by high-throughput mold - Jiarun Qin; Wenchao Yang; Chen Liu; Qiang Wang; Zhao Xin; Yanchao Zhang; Yang Liu; Haijun Su; Lin Liu (Journal of Materials Research and Technology, 2025)
The secondary orientation effect of platform defects was investigated in single crystal blades with different secondary orientations. The results showed that the orientations of the two groups of blades were well controlled, and the defects formed in the platform of (0o, 0o) orientation blades were mainly deformation dendrites, while those for blades with (0o, 26.5o) orientation were stray grains and large broken dendrites. For stray grains, it was found that the blades with (0o, 0o) orientation could allow the dendrites to occupy the platform space earlier, thus inhibiting the nucleation of stray grains, while the blades with (0o, 26.5o) orientation exhibited the opposite behavior. Besides, it was revealed that the shrinkage stress only caused the small broken dendrites at the corner, but did not induce deformation or large broken dendrites. Combined with fluid flow simulation, it was seen that the deformation dendrites for (0o, 0o) orientation blades were mainly formed at the initial stage of solidification, where the degree of convection was relatively uniform and low. However, the large broken dendrites for (0o, 26.5o) orientation blades were mainly formed at the later stage, where the thermal knots had increased the melt convection, making dendrites more prone to fracture.